2012
DOI: 10.1007/s10973-012-2641-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, spectroscopic, and dissolution studies of the simvastatin–acetylsalicylic acid mixtures

Abstract: The objective of the present investigation was to study the effect of eutectic formation on in vitro dissolution of simvastatin (SIM) released from mixtures with acetylsalicylic acid (ASA) prepared by a grinding method. SIM-ASA mixtures were characterized by means of differential scanning calorimetry (DSC), infrared spectroscopy (IR), X-ray powder diffractometry (XRPD), and in vitro dissolution tests. IR spectroscopy and XRPD studies indicated no interaction between SIM and ASA in the solid state. The DSC inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Our previous studies have shown that ASA as a second component in the drug-drug binary mixtures positively affects the dissolution rate of components. So that binary mixtures of fenofibrate/aspirin, simvastatin/aspirin and lovastatin/ aspirin are characterized by an increased dissolution rate of fenofibrate, simvastatin or lovastatin, observed at the eutectic formation region [20][21][22]. Although simple combinations of EZT-ASA have not yet been described, many studies emphasize that co-administration of two active pharmaceutical ingredients in one dosage form in comparison with the administration of two single tablets could increase patient compliance, which is the goal in the therapy of cardiovascular diseases [8,23].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that ASA as a second component in the drug-drug binary mixtures positively affects the dissolution rate of components. So that binary mixtures of fenofibrate/aspirin, simvastatin/aspirin and lovastatin/ aspirin are characterized by an increased dissolution rate of fenofibrate, simvastatin or lovastatin, observed at the eutectic formation region [20][21][22]. Although simple combinations of EZT-ASA have not yet been described, many studies emphasize that co-administration of two active pharmaceutical ingredients in one dosage form in comparison with the administration of two single tablets could increase patient compliance, which is the goal in the therapy of cardiovascular diseases [8,23].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of solid dispersions is one of the most effective and convenient techniques used for solubility enhancement of poorly soluble drugs [11][12][13]. Several approaches have been employed to improve the solubility of ketoconazole [8], such as preparation of solid dispersions with polyvinlypyrrolidone 17 (PVP 17) and PVP-vinyl acetate (PVP-VA64) copolymer prepared by melt extrusion [14], solid dispersions with nicotinamide [15], and inclusion complexation of ketoconazole in bcyclodextrin obtained by solvent evaporation method [5].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained in vitro dissolution results indicate that the formation of lovastatin solid dispersions with ASA could be a promising approach to improve its release from oral dosage form, and hence may affect its bioavailability. The improvement of the LOV dissolution rate does not depend directly on a eutectic composition, as in the case of simvastatin [27], that has water solubility one order of magnitude better (30 lg mL -1 [32]) than LOV, but the formation of eutectic in the LOV-ASA system naturally promotes the effective wetting of the reduced drug particles released from eutectic composition. The results of our investigation show that lovastatin dissolution rate can be improved by the formation of solid dispersions with ASA without chemical interaction between the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of carriers have been employed in the preparation of lovastatin solid dispersions in order to improve the solubility of LOV, such as mannitol [18], Poloxamer F68 [19], polyethylene glycol 4000 and 6000, (PEG 4000, PEG 6000), polyvinylpyrrolidone K30 (PVP K30) [20,21], sodium starch glycolate, croscarmellose sodium, crospovidone [22,23], locust bean gum [24] and soluplus [25], but no reports exist on forming lovastatin solid dispersions with other APIs. Our previous research into binary mixtures of fenofibrate or simvastatin with ASA showed an appreciable increase in the API dissolution rate in relation to eutectic formations [26,27]. In light of this, the aim of the present study was to characterize the solid state of the prepared LOV/ASA solid dispersions by DSC, FTIR and XRPD, as well as to assess the formation of LOV/ASA solid dispersions on the dissolution rate of both ingredients.…”
Section: Introductionmentioning
confidence: 92%